PEMAHAMAN SUNNAH MUHAMMAD SYAHRUR DAN PENGEMBANGAN ILMU HADIS - Zainal Abidin (Institut Keislaman Abdullah Faqih Gresik, 2017)
This article examines Muhammad Syahrur's understanding of the Sunnah which is deemed perverted but has a contribution to the development of the science of hadith. The method used in this study is a descriptive qualitative method using a library study approach and content analysis. Literature study is used to examine the Sunnah understanding according to Muhammad Syahrur to the Sunnah of the Prophet. in his book Nahwa Usul Jadidah Lil Fiqh Al-Islami then made a grand theory to reveal the understanding of the contribution to the science of hadith. The data sources used are primary data sources and secondary data sources. While the theory of data analysis and processing uses content analysis. The findings show: first, rationalizing sunnah/traditions that contradict human reason; second, understanding of the Sunnah by Muhammad Syahrur integrating science and breaking scientific linearity; third, the concept of understanding the Sunnah of Muhammad Syahrur can be considered as an attempt to uncover the chaos of the study of the science of hadith.Keywords: Science of hadith, Sunnah, Muhammad Syahrur